Risk Mitigation Analysis in the Construction of Dormitories for Students of Riyadlus Sholihin Islamic Boarding School, Probolinggo City - Aditya, Febri; Witjaksana, Budi; Sajiyo, Sajiyo (International Journal Labs, 2025)
The implementation of construction projects often faces various risks that can lead to delays, cost overruns, and decreased quality of work. One example occurred in the project to build a dormitory for students of the Riyadlus Sholihin Islamic Boarding School in Probolinggo City, which experienced a time deviation despite acceleration efforts. This shows the importance of implementing systematic risk management to identify and address potential risks from the beginning of project implementation. This study uses a descriptive quantitative approach through the dissemination of questionnaires and interviews to related parties in the project. The analysis was carried out using the Severity Index method to calculate the level of probability and impact of each risk, as well as the probability and impact matrix to determine the level of risk significance. The dominant risk is then further analyzed to determine mitigation actions. The results of the study showed five risks with a